Pengaruh Kualitas Produk dan Harga Terhadap Keputusan Pembeli Kosmetik Make Over (Studi Kasus Pada Konsumen Toko Eka Kosmetik Lahat): Pengaruh Kualitas Produk dan Harga Terhadap Keputusan Pembeli Kosmetik Make Over (Studi Kasus Pada Konsumen Toko Eka Kosmetik Lahat) (Ekonomika, 2021)
The title of this research is "The Effect of Product Quality and Price on Buyer Decisions of Cosmetics Make Over (Case Study on Consumers of Eka Cosmetics Stores)". The purpose of this study was to determine and analyze the effect of product quality on purchasing decisions for Make Over cosmetics on Eka Cosmetics Shop consumers, to determine and analyze the effect of price on purchasing decisions for Make Over cosmetics on Eka Cosmetics Shop consumers and to determine and analyze the effect of product quality and price. on the decision to buy Make Over cosmetics at Eka Cosmetics Shop consumers. Primary data in this study were obtained by distributing questionnaires to 80 consumers of Eka Cosmetics Shop. The data analysis technique used was the SPSS version 23.0 application, using data testing and statistical testing. From the results of data analysis on the variables studied, namely product quality and price, it shows that there is an influence on the purchasing decision of Make Over cosmetics on Eka Cosmetics Shop Consumers simultaneously and partially.